First records of Archiconnus and Obesoconnus in Costa Rica (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2018)
The occurrence of the glandulariinae genera Obesoconnus and Archiconnus in Costa Rica is reported for the first time. Obesoconnus was previously known from Mexico and French Guyana; Obesoconnus costaricanus sp. n. fills the gap in the hitherto known distribution of this remarkable genus. Archiconnus was known only from the northern part of Peru (east of the Andes); Archiconnus limonensis sp. n. broadens the known genus range 2000 km to north-west.